The Effectiveness of Dental Health Cadre Training on Increasing the Knowledge of Village Community Dental Health Cadres (UKGMD) in Karangtengah Village, Baturraden District - Hidayah, Riski Amalia; Oktadewi, Fitri Diah; Hartomo, Bambang Tri; Fithriyya, Naila Robbaniyya; Cahyani, Inneke (Kesmas Indonesia, 2024)
Village Community Dental Health Efforts (UKGMD) is one of the breakthrough efforts or strategies to assist the community in reaching dental health services that have not been implemented yet and encourage the community to provide dental health services at the nearest health service. Dental and oral health survey data for the people of Karangtengah Village, Baturraden District in 2019 show an average caries with a DMF-T index of 13.12 which is classified as a very high category according to WHO. The cadre training activities were attended by 28 representative cadres from 7 posyandu in Karangtengah Village. Training activities include providing material through audio-visual forms and practice accompanied by the team. The assessment of this activity is carried out through the results of the pretest at the beginning of the activity session and the postest assessment at the end. The results of the pretest and postest showed an increase in the average knowledge score of cadres from 7.92 ± 1.56 to 8.85 ± 0.57. The paired t-test statistical test showed that there was a significant difference between the level of knowledge of cadres before and after receiving the training materials (p<0.05). The results showed that cadre training effectively increased UKGMD cadres' knowledge about oral health and simple dental examination methods.